Study of Local Wisdom Based on Disaster Mitigation in the Community of Traditional Villages in West Java as Materials in History Learning - Darmawan, Wawan; Mulyana, Agus; Kurniawati, Yeni (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2022)
Livestock, and the harmonious relationship between humans/communities and the natural surroundings. This paper examines several local pearls of wisdom related to disaster mitigation in the lives of the people of West Java. Mitigation can build a culture of reaction to a culture of prevention, or from acting after the incident to acting before the incident. The study becomes interesting by searching for local wisdom of disaster mitigation still growing in the community. This study uses a qualitative descriptive method that describes the research subject in the field. Part of the data was obtained by observation before the COVID-19 pandemic and partly from the documentation. Furthermore, it is analyzed through data reduction, verification, and presentation. The results showed that the traditional village communities in West Java, such as Kampung Adat Naga, Kampung Adat Ciptagelar, Kampung Adat Cireundeu, Kampung Adat Polo, and Kampung Adat Kuta, have local wisdom in disaster mitigation which is implemented in the construction of houses, prohibition forests, prohibition of raising animals. The local wisdom of disaster mitigation is reinforced by myths with magical nuances that have strong potential in protecting the surrounding natural environment. Local wisdom can be a form of indirect awareness and has meaning in dealing with disaster threats to reduce disaster risk.